2016
DOI: 10.1177/1687814016667679
|View full text |Cite
|
Sign up to set email alerts
|

Design of in-pipe robot based on inertial positioning and visual detection

Abstract: The horizontal directional drilling technology is widely used to lay the underground pipelines. These pipelines are of small or medium diameters with a dip angle ranging from 10°to 20°, special pipelines to 30°. In-pipe robot is commonly used to detect the pipeline fault. A new type of telescopic in-pipe robot is designed in this article, which is driven by step motor and screw, and supported by wheels. The robot has advantages of waterproof grade of IP68, stable motion state, and larger traction force. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…When the robot moves in the curved pipe, the length and width of the robot must satisfy geometric conditions. 17 We found that the maximum length of the robot is related to the relative shape configurations, as indicated in Figure 17. We investigated four typical conditions, let R be the radius of the elbow curvature, D is the diameter of the pipe and d e be the span angle of the curve section.…”
Section: Posture B In the Elbowmentioning
confidence: 79%
“…When the robot moves in the curved pipe, the length and width of the robot must satisfy geometric conditions. 17 We found that the maximum length of the robot is related to the relative shape configurations, as indicated in Figure 17. We investigated four typical conditions, let R be the radius of the elbow curvature, D is the diameter of the pipe and d e be the span angle of the curve section.…”
Section: Posture B In the Elbowmentioning
confidence: 79%
“…This problem is not new and some solutions have been brought to an incipient market. Works as those in [1,2] propose the creation of a map of the pipe set navigating among it with odometry and inertial units [3]. Obstacle avoidance in a crowded 3D world of pipes becomes of great interest when planning a flight; in [4], some contributions are made in this direction although the accuracy of object is deficient to be a reliable technology.…”
Section: Introductionmentioning
confidence: 99%
“…Through force analysis and calculation, its maximum climbing angle is larger than 35°. The robot has good passing ability through the pipelines with bends [20]. Obstacle avoidance is not considered in previous researches.…”
Section: Introductionmentioning
confidence: 99%